Drug abuse in athletes - Reardon CL; Creado S (Dove Medical Press, 2014)
Claudia L Reardon, Shane Creado Department of Psychiatry, University of Wisconsin School of Medicine and Public Health, Madison, WI, USA Abstract: Drug abuse occurs in all sports and at most levels of competition. Athletic life may lead to drug abuse for a number of reasons, including for performance enhancement, to self-treat otherwise untreated mental illness, and to deal with stressors, such as pressure to perform, injuries, physical pain, and retirement from sport. This review examines the history of doping in athletes, the effects of different classes of substances used for doping, side effects of doping, the role of anti-doping organizations, and treatment of affected athletes. Doping goes back to ancient times, prior to the development of organized sports. Performance-enhancing drugs have continued to evolve, with “advances” in doping strategies driven by improved drug testing detection methods and advances in scientific research that can lead to the discovery and use of substances that may later be banned. Many sports organizations have come to ban the use of performance-enhancing drugs and have very strict consequences for people caught using them. There is variable evidence for the performance-enhancing effects and side effects of the various substances that are used for doping. Drug abuse in athletes should be addressed with preventive measures, education, motivational interviewing, and, when indicated, pharmacologic interventions. Keywords: doping, athletes, steroids, drug abuse, mental illness